2022
DOI: 10.21930/rcta.vol23_num1_art:2361
|View full text |Cite
|
Sign up to set email alerts
|

Aislamiento y caracterización de Metarhizium spp. de cultivos de caña de azúcar y su patogenicidad contra Mahanarva andigena (Hemiptera: Cercopidae)

Abstract: Metarhizium anisopliae es uno de los hongos entomopatógenos más comercializados para la regulación de poblaciones de insectos plagas. Las cepas nativas de este hongo ejercen un importante rol en el control natural. Sin embargo, se desconoce su efectividad en condiciones amazónicas ecuatorianas. Es por ello que esta investigación tuvo como objetivos aislar y caracterizar cepas nativas de M. anisopliae con potencial para el control de Mahanarva andigena (Jacobi) en el cultivo de caña de azúcar (Saccharum officin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…spore conidia ranged from 2.7 to 7.8 µm in length and from 0.8 to 2.8 µm in width. However, Valle-Ramírez et al [29] reported higher values ranging from 5.08 to 7.19 µm in length and between 2.02 and 3.24 µm in width for Metarhizium conidia isolated from sugarcane crops in Ecuador. These differences highlight the need for molecular analysis in future studies since, although the conidia belong to the same genus, they could be of different species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…spore conidia ranged from 2.7 to 7.8 µm in length and from 0.8 to 2.8 µm in width. However, Valle-Ramírez et al [29] reported higher values ranging from 5.08 to 7.19 µm in length and between 2.02 and 3.24 µm in width for Metarhizium conidia isolated from sugarcane crops in Ecuador. These differences highlight the need for molecular analysis in future studies since, although the conidia belong to the same genus, they could be of different species.…”
Section: Discussionmentioning
confidence: 97%
“…The morphological and physiological characteristics evaluated by Padilla et al [19] and Valle-Ramírez et al [29] were considered for the identification of the isolate genus; these characteristics included colony edge and texture, color and pigmentation, spore length and width, radial growth, conidial concentration, and germination percentage. However, these characteristics may differ between isolates due to the genetic diversity observed when collecting and isolating in different geographical locations [30].…”
Section: Discussionmentioning
confidence: 99%